Cephoids: Minkowski sums of prisms - Diethard Pallaschke; Joachim Rosenmüller (Bielefeld University, Institute of Mathematical Economics (IMW), 2004)
We discuss the structure of those polytopes in Rⁿ+ that are Minkowski sums of prisms. A prism is the convex hull of the origin and n positive multiples of the unit vectors. We characterize the defining outer surface of such polytopes by describing the shape of all maximal faces. As this shape resembles the view of a cephalopod, the polytope obtained is called a 'cephoid'. The general geometrical and combinatorial aspects of cephoids are exhibited.
urn:nbn:de:hbz:361-6266
Keywords: 330